"d-Prose 1870–1920" a Collection of German Prose Texts from 1870 to 1920. (8th July 2021) - Gius, Evelyn; Guhr, Svenja; Uglanova, Inna
The corpus "d-Prose 1870-1920" is a heterogeneous collection of 2511 German-language literary prose texts published between 1870 and 1920. It contains narrative texts from trivial and high literature with a minimum length of 1000 words. The texts are available as UTF-8 text files with an associated metadata table. These data are primarily of interest to literary scholars, linguists, but also for all those who are involved in the modelling of textual and cultural phenomena. The corpus can be used to test literary, literary-historical, cultural, and linguistic hypotheses.